A ingestão aguda de paroxetina modula os mecanismos de fadiga durante o exercício em indivíduos com diferentes capacidades aeróbicas - Francisco Teixeira Coelho (2009)
The purpose of the present study was to investigate the influence of aerobic capacity on the relationship between central serotonergic system and fatigue during prolonged exercise in young men. Sixteen volunteers were divided in two groups (n=8, each group): high aerobic capacity (23.8 ± 0.77 years; VO2peak = 42.84 ± 0.85 mL.kg- 1.min-1) and low aerobic capacity subjects (23.63 ± 0.60 years; VO2peak 57.32 ± 1.02mL.kg-1.min-1). An incremental test in a cycle ergometer with direct measures of oxygen consumption was performed to determinate the aerobic capacity of the subjects. Six days after the incremental test, the volunteers were submitted to four experimental trials in which they ingested placebo, 10, 20 or 40 mg of paroxetine, an inhibitor of theserotonin reuptake. The order of the trials was balanced and crossed, and care was taken to ensure that both the investigator and the volunteer remained blinded to the solution ingested throughout the experiments. The trials were separated by an interval of at least seven days. On the day of the experiment, all the meals (breakfast, lunch and a snack) offered to the volunteers, were controlled and standardized by the investigator.Four and half hours after the ingestion of the drug / placebo, the subjects cycled until fatigue at 60% of the maximal power measured during the incremental test. None of the three paroxetine concentrations influenced the time to fatigue in the low aerobic capacity group (PLA = 48.83 ± 4.57 min; 10 mg = 48.93 ± 6.99 min; 20 mg = 46.45 ± 5.68 min; 40 mg = 42.02 ± 5.40 min). On the other hand, for the group of higher aerobic capacity,time to fatigue was reduced only in the 20 mg of paroxetine trial (PLA = 89.96 ± 7.88 min; 10 mg = 86.28 ± 7.49 min; 20 mg = 76.25 ± 5.10 min; 40 mg = 81.46 ± 8.28 min). When comparing both groups, the time to fatigue was always higher in high aerobic capacity group. Therefore we concluded that aerobic capacity modulates the activity of the serotonergic system and, consequently, its relationship with fatigue during prolongedexercise in humans. However, different from the literature, the serotonergic system of high aerobic capacity subjects does not seem to present an attenuated activation during the exercise when compared to the low aerobic capacity subjects.